Depression screening and referral in cardiac wards: A 12-month patient trajectory. (1st February 2017) - Ski, Chantal F; Worrall-Carter, Linda; Cameron, Jan; Castle, David J; Rahman, Muhammad A; Thompson, David R
Abstract: Background: Depression is common among patients with coronary heart disease (CHD) and has a major impact on their quality of life, morbidity and mortality. Aim: The aim of this study was to map the 12-month psychosocial outcomes of patients with CHD who were screened positive for depression in an acute cardiac ward. Methods: A prospective cohort study was conducted of the psychosocial trajectory (depression, anxiety, wellbeing, social support, mental health service access) of 212 patients with CHD who were screened for depression after being admitted to acute cardiac wards of a major metropolitan hospital. Outcomes were assessed before hospital discharge and at one, three, six and 12 months post-discharge. Results: Linear mixed models identified that those patients screened at 'moderate to high' risk of depression at baseline had higher levels of depression ( F (1, 173)=53.93, p <0.0001) and anxiety ( F (1, 180)=67.01, p <0.001), and lower levels of wellbeing ( F (1, 186)=42.47, p <0.001) and social support ( F (1, 177)=25.40, p <0.0001), compared to those at 'no to low' risk of depression. Levels of depression and wellbeing remained fairly constant over the 12-month trajectory. Surgical and medical treatment groups were of similar psychological composition over the 12-month period. Conclusions: These findings attest to the effectiveness and predictive validity of a simple nurse-administered screening tool designed to identify depression in hospital patients with CHD and also indicate that a screening and referral tool alone is not sufficient to achieve optimal disease management. A collaborative care model involving family members and integrated pathways to primary care is recommended.